Rate of X chromosome aneuploidy in young fertile women: Comparison of cultured and uncultured cell preparations using fluorescence in situ hybridisation - Patton, K.; Murch, A.; Goldblatt, J.; Wetherall, John; Doherty, D.; Hadlow, N. (Blackwell Publishing, 2010)
Background: X chromosome aneuploidy <10% in female patients is a routinely used reporting limit in diagnostic cytogenetics. X aneuploidy (<10%) is commonly detected in women investigated for infertility or recurrent miscarriages. It is unclear if this aneuploidy is causally relevant or related to the culture process. Information about the background rate of X aneuploidy in young fertile women would be helpful in resolving this issue. Aim: This study aimed to investigate the rate of X aneuploidy in young fertile women in cultured and uncultured samples to determine if the commonly used <10% limit is relevant. Method: Volunteers (aged 22–40 years) with proven fertility (n = 78) participated. The number of X chromosome signals in 500 cultured and 500 uncultured preparations were enumerated using FISH.Results: Significantly, all participants had <5% X aneuploidy in both preparations, X chromosome loss occurred (2.4%) more frequently than gain (0.7%). Cultured preparations had a mean of 2.1% cells with X chromosome aneuploidy (95% CI 1.9–2.3%) compared with a mean rate of 0.9% aneuploidy in uncultured preparations (95% CI 0.7–1.1%). The relative risk for cultured preparations having X aneuploidy compared with uncultured cells was 2.33 (P < 0.001) (95% CI 2.1–2.6). Conclusion: Young fertile women had <5% X aneuploidy. The rate of X aneuploidy was higher in cultured (2.1%) compared with uncultured (0.9%) preparations (P < 0.001). This data may provide useful background information when considering low level X aneuploidy in other groups of women with clinical indications for karyotype.